A comparative study about motivations, expectations and future plans for professional development in four European radiography programs - Sá dos Reis, Cláudia; Pires Jorge, J.; York, H.; Flaction, L.; Johansen, S.; Mæhle, S. (W.B. Saunders Co. Ltd., 2018)
Introduction: This study aims to compare motivations, expectations and work plans of students and teaching-staff from four different European radiography programs, it aims also to explore areas that could be included to advance post graduate studies. Methods: Two different questionnaires (open- and closed-end questions) were applied to key-informants, students who had just completed their bachelor thesis and teaching-staff, to collect data regarding motivations, expectations, challenges and potentials for radiography education and, plans for further work. Descriptive statistics and thematic analysis were performed according to the nature of the questions. Results: The response rates were 45% (students) and 68% (teaching-staff). The motivations to study radiography were similar between students: to work in a healthcare-service, helping people, manipulating high-end technologies, providing service while combining different knowledge (physics, patient-care, physiology, anatomy). 75% of the students did not reach all their expectations due to the lack of focused and updated content for some areas. The teaching-staff were expecting an extension of the radiographers' role. The development of advance studies in computed tomography and magnetic resonance was highlighted as important by students. Future work plans included: self-improvement, continuation of studies, specialization, research and collaborations. Conclusions: This study increased the understanding of radiography education and provides insights into future perspectives. Participants have similar motivations, expectations and future plans. Improvements in education should focus on technological developments and meeting job market demands. Further studies should be performed to identify approaches that acknowledge the specific needs of each country, while also providing strategies to harmonize radiography education in Europe.